Uterocervical Angle Measurement Improves Prediction of Preterm Birth in Twin Gestation - Knight, Jordan C.; Tenbrink, Emily; Onslow, Mitchell; Patil, Avinash S. (American Journal of Perinatology, 2018)
Objective Twin pregnancies are associated with an increased risk of spontaneous preterm birth. Our objective was to compare the performance of uterocervical angle to cervical length as predictors of spontaneous preterm birth in this population.Methods We conducted a retrospective cohort study of twin gestations at a single center from May 2008 to 2016 who received a transvaginal ultrasound for the evaluation of the cervix between 16 0/7 and 23 0/7 weeks. The primary outcome was prediction of preterm birth <28 and <32 weeks by uterocervical angle and cervical length.Results Among 259 women with twin gestation, the mean gestational age at birth was 34.83 ± 3.48 weeks. Receiver operator characteristic curves demonstrated optimal prediction of spontaneous preterm birth prior to 32 weeks at a uterocervical angle >110° (80% sensitivity, 82% specificity) [odds ratio (OR), 15.7 (95% confidence interval (CI), 7.2–34.4)] versus cervical length <20 mm (53% sensitivity, 85% specificity; p < 0.001, OR, 6.4 [95% CI, 2.3–17.8]) and similarly, prior to 28 weeks at a uterocervical angle >114° (OR, 24.3 [95% CI, 6.7–88.5]) compared with cervical length <20 mm (OR, 11.4 [95% CI, 3.5–36.7]).Conclusion Uterocervical angles >110° performed better than cervical length for the prediction of spontaneous preterm birth in twin gestations.
Keywords: cervical length; multiple gestation; preterm birth; ultrasound; uterocervical angle